PROSES KREATIVITAS SISWA DALAM PEMBELAJARAN SENI RUPA KELAS V SD NEGERI 1 MONTONGSARI - Niken Apriani; Prasena Arisyanto; Riris Setyo Sundari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to reveal how the creativity process of grade V students ini participating in fine arts learning at SD Negeri 1 Montongsari. The research is motivated by the lack of attention to the process of student creativity, because fine arts learning tends to emphasize the final result of the work. This research uses descriptive qualitative methods with data collection techniques in the form of observation, interview, and documentation. The reserch findings reveal that although fine arts learning has referred to an independent curriculum, it has not been fully directed to develop student creativity. In addition, this activity also plays a role in fostering positive character values such as responsibility, cooperation and independence. Therefore, a more explorative and student-centered learning approach is needed so that the potential for creativity can be developed to the fullest.